2021
DOI: 10.1007/jhep11(2021)218
|View full text |Cite
|
Sign up to set email alerts
|

Probing charged lepton flavor violation with axion-like particles at Belle II

Abstract: We study charged lepton flavor violation associated with a light leptophilic axion-like particle (ALP), X, at the B-factory experiment Belle II. We focus on production of the ALP in the tau decays τ → Xl with l = e, μ, followed by its decay via X → l−l+. The ALP can be either promptly decaying or long-lived. We perform Monte-Carlo simulations, recasting a prompt search at Belle for lepton-flavor-violating τ decays, and propose a displaced-vertex (DV) search. For both types of searches, we derive the Belle II s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…In refs. [11][12][13][14], the dark photon production from the dark Higgs decay at the FASER and other experiments [15][16][17][18] was studied. Using a large number of the dark Higgs bosons produced by heavy meson decays through the scalar mixing with the SM Higgs boson, it was shown that the sensitivity to the dark photon parameters can be enlarged.…”
Section: Introductionmentioning
confidence: 99%
“…In refs. [11][12][13][14], the dark photon production from the dark Higgs decay at the FASER and other experiments [15][16][17][18] was studied. Using a large number of the dark Higgs bosons produced by heavy meson decays through the scalar mixing with the SM Higgs boson, it was shown that the sensitivity to the dark photon parameters can be enlarged.…”
Section: Introductionmentioning
confidence: 99%
“…In [43][44][45], on the other hand, one finds a more generic analysis of ALP signatures in cLFV phenomena, where both muonic and tauonic decay modes are entertained. Searches for τ → ℓX at Belle II are also expected to play a major part in the ongoing probing of flavourviolating new physics, either via prompt decays of possibly short-lived ALPs or, in the case of long-lived ALPs, via displaced vertices or missing energy [46,47]. These processes are, however, beyond the scope of the present work.…”
Section: Introductionmentioning
confidence: 91%
“…The expected number of signal events in the signal bin depends on the µ + → e + X branching ratio B as nr s = B N µ E s I s = B N b E I s , where I s is defined in analogy to (46). Using the LO approximation H s (E ′ ) ∝ δ(E ′ − E X ), we have I s = erf(z 90 / 2) = 0.9.…”
Section: Experimental Sensitivitymentioning
confidence: 99%
“…Signatures of directly detectable or escaping long-lived particles at B factories have also been discussed in refs. [30,[46][47][48][49][50][51][52][53][54][55][56][57][58][59] This paper is organized as follows: section 2 contains the theoretical framework of the RPV scenario. This includes the effective Lagrangian with the RPV terms and the calculation of the matrix elements, which we estimate using an effective BNV Lagrangian.…”
Section: Jhep02(2023)224mentioning
confidence: 99%